Suryanamaskar performed for a shorter duration matches the exercise intensity of a regular physical education session in adolescent children: A cross-over study - Apurv P Shimpi; Jaimala Vijay Shetye; Meenakshi Sureshlal Kewlani (Wolters Kluwer Medknow Publications, 2022)
Context: Adolescent children are provided with lesser exercise duration and intensity due to academic priorities. Suryanamaskar (SN) may be a time-saving solution for their fitness enhancement. Aim: To determine the duration and number of SN required by adolescent children to match the exercise intensity of their regular physical education (PE) session. Materials and Methods: A cross-over study was conducted on 50 children, both genders, with a mean age of 13.9 ± 0.7 years, by a simple random sampling process. Their pulse rate (PR), respiratory rate (RR), and rate of perceived exertion (RPE) were measured pre- and immediately post participation in their routine PE session. After 24-h washout period, participants performed slow 12-step SN to match the PE session RPE post which their PR, RR, and number of SN performed were measured. Furthermore, their weekly duration of involvement in PE was documented. The PR, RR, and duration of PE/SN were compared using unmatched t-test with α set at ≤0.05 at 95% confidence interval. Results: Adolescent children achieved RPE of 1.9 ± 1.4 post a 33.0 ± 9.0 min PE session which was matched in 9.4 ± 2.3 min of SN session (p < 0.05) at a similar PR (p = 0.25) and RR (p = 0.08). These children were found to be engaged in 75.6 ± 20.3 min of PE activity/week. Conclusion: A 9-min session consisting of nine SN matches the exercise intensity of a routine 33-min PE session in adolescent children.